Sinsajo - Collins, Suzanne; Ramirez Tello, Pilar (Barcelona : Molino/RBA Libros, 2012)
Against all odds, Katniss Everdeen has survived the Hunger Games twice. But now that she's made it out of the bloody arena alive, she's still not safe. The Capitol wants revenge ... and President Snow has made it clear that no one else is safe!
Keywords: Insurgency -- Fiction; Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction; Insurreccion -- Novela; Supervivencia -- Novela; Programas de television -- Novela; Relaciones humanas -- Novela; Competencias -- Novela